Gender Representation in Nepali Commercials - Paneru, Pragya (Pravaha, 2021)
This paper explores gender representation in visual media, especially in commercials broadcasted through various Nepali visual media. A content analysis of twenty-one commercials was done underpinning gender and feminist perspectives to explore gender representation in them. The advertisement samples were selected among some popular brands and the products of everyday use. The findings suggested reinforcement of traditional gender roles and reproduction of gender hierarchies by depicting men and women in traditionally specified roles, appearances, and concepts. Cooking, washing, and childcare were regarded as female jobs. More men were depicted in occupational roles and females were projected in relational roles. This research is based on the claim that biased gender representations in media sustain gender bias attitudes on viewers thus a careful selection of gender-neutral or counter-stereotypical content should be promoted.